TEACHING GRAMMAR WITH OSCAR WILDE - Basilius Himawan Setyo Wibowo (Widya Mandala Surabaya Catholic University, 2022)
In English teaching, there has been a dichotomy between language and literature. Literature is sometimes perceived as isolated from language. Teachers of English are reluctant to teach literature feeling that they do not possess the competence in literature. Teachers of literature feel similar reluctance due to the perception that they do not master grammar adequately. This article tries to find a possible way of teaching English grammatical aspects through literary works by adopting Carlson and Tovatt’s way of reading.